The “Jew,” the Nation and Assimilation: The Old Testament and the Fashioning of the “Other” in German and Dutch Protestant Thought - Tol, Mariëtta van der (Journal of the bible and its reception, 2021)
This article discusses a reorientation of supersessionist postures in German and Dutch Protestant reflection on emerging nation states in the nineteenth-century. Historically, Christian thought often othered “the Jew” as the “nascent Christian.” Since the seventeenth-century, Protestant theologians also entertained the possibility of theological othering on the basis of the legalism of the Mosaic covenant, of which ancient biblical Israel and its cultural liturgies were regarded as a token. In the context of the modern nation, German and Dutch Protestant thought entertained this typological othering of biblical nationhood to construct the modern Jew as “Gentile” to the modern nation. As “Gentile,” “the Jew” remains the embodiment of the ultimate other, yet as “nascent Christian,” modern Jews begin to face an unrelenting demand to assimilate. This conundrum contributed to a fundamental tension in the imaginary of the nation, namely between patterns of othering and structures of belonging, echoing far beyond antisemitism, and especially in patterns of othering that are inherent to racism and Islamophobia.